The Use of Pomalidomide in the Treatment of Relapsed/Refractory Multiple Myeloma in Patients with Renal Failure - IG Rekhtina; MV Nareiko; LP Mendeleeva (Клиническая онкогематология)
The present review includes data on efficacy and safety of pomalidomide, an immunomodulating 3rd generation drug used for treatment of relapsed and refractory multiple myeloma patients with renal failure. The results of multicenter randomized trials proved similar efficacy and comparable safety profile in patients with normal renal function and patients with moderate and/or severe renal failure. All patients received the standard starting dose. Pomalidomide dose needs to be reduced in response to hematological toxicity. The paper provides practical guidelines on the use of pomalidomide and treatment of adverse events adopted by consensus of international experts. Current approaches to multiple myeloma with renal failure, and the use of pomalidomide in particular, are demonstrated by means of a clinical case.